2022
DOI: 10.29039/rusjbpc.2022.0512
|View full text |Cite
|
Sign up to set email alerts
|

Benzoate Group Attachment to Tempo Provides Enhanced Discrimination of Liposomes Fabricated Using Human Lung Normal and Carcinoma Cells

Abstract: It is widely accepted that the lipid compositions of the plasma membranes of healthy and cancer cells significantly differ from each other. During the cancer progression, cancer cells change the lipid constituent of the membranes resulting in the loss of lipid asymmetry between the membrane leaflets. Consequently, physicochemical properties of the cell membranes are also changed in response to altered lipid organization. Partitioning of the spin probe 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) into the membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
0
3
2
Order By: Relevance
“…The study revealed differences in parameters (polarity, micro-viscosity, and the energy required to transfer TEMPO from the aqueous to the membrane environment) between the membranes of cancer and healthy cells. Compared with previous works on liposomes [ 26 , 27 ], the results obtained in this study indicate that pro teins embedded in the cell membranes significantly alter the dynamics of the lipid fraction, making them more dynamic and permeable to small molecules. The determined temperature and pH sensitivities of the cell membranes may help to choose or create the appropriate conditions for cancer therapy.…”
Section: Introductioncontrasting
confidence: 74%
See 4 more Smart Citations
“…The study revealed differences in parameters (polarity, micro-viscosity, and the energy required to transfer TEMPO from the aqueous to the membrane environment) between the membranes of cancer and healthy cells. Compared with previous works on liposomes [ 26 , 27 ], the results obtained in this study indicate that pro teins embedded in the cell membranes significantly alter the dynamics of the lipid fraction, making them more dynamic and permeable to small molecules. The determined temperature and pH sensitivities of the cell membranes may help to choose or create the appropriate conditions for cancer therapy.…”
Section: Introductioncontrasting
confidence: 74%
“…Therefore, the use of TEMPO in membrane research allows for a selective characterization of the lipid phase. Unlike the findings obtained in liposomes [26,27], in this case, lipid phase properties are modified by the membrane proteins of the corresponding cells. Below, we provide experiments of TEMPO partitioning into the membranes of the cells at the temperature of 283-317 K interval and pH values of 7.3 and 6.2, conditions that are relevant for cancer therapeutics.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations